2019
DOI: 10.1002/cam4.2101
|View full text |Cite
|
Sign up to set email alerts
|

Nrf2 in cancers: A double‐edged sword

Abstract: The Nrf2/Keap1 pathway is an important signaling cascade responsible for the resistance of oxidative damage induced by exogenous chemicals. It maintains the redox homeostasis, exerts anti‐inflammation and anticancer activity by regulating its multiple downstream cytoprotective genes, thereby plays a vital role in cell survival. Interestingly, in recent years, accumulating evidence suggests that Nrf2 has a contradictory role in cancers. Aberrant activation of Nrf2 is associated with poor prognosis. The constitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
326
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 363 publications
(332 citation statements)
references
References 171 publications
3
326
0
3
Order By: Relevance
“…Activation of the NRF2 system is complex and can follow canonical and non-canonical pathways. A difficulty in identifying activators and inhibitors of NRF2 or KEAP1 as modulators of inflammation and potential protectors against oxidative stress and carcinogenesis, is the dual nature of the NRF2-KEAP1 protein-protein interaction [26,[59][60][61][62]. Generally, activation of NRF2 has been viewed as therapeutic, but recent evidence has suggested that this event can be pro-oncogenic as well, depending on the context of NRF2 activation [62].…”
Section: Activators Of Nrf2mentioning
confidence: 99%
See 3 more Smart Citations
“…Activation of the NRF2 system is complex and can follow canonical and non-canonical pathways. A difficulty in identifying activators and inhibitors of NRF2 or KEAP1 as modulators of inflammation and potential protectors against oxidative stress and carcinogenesis, is the dual nature of the NRF2-KEAP1 protein-protein interaction [26,[59][60][61][62]. Generally, activation of NRF2 has been viewed as therapeutic, but recent evidence has suggested that this event can be pro-oncogenic as well, depending on the context of NRF2 activation [62].…”
Section: Activators Of Nrf2mentioning
confidence: 99%
“…Whereas new findings indicate that NRF2 plays a dual role in cancer ( [26,105,106], the potential use of NRF2 activators in cancer prevention and therapy needs to be further elucidated. It is widely accepted that effective chemoprevention should encompass induction of cytoprotective and detoxifying enzymes.…”
Section: Potential Use Of Nrf2 Activators In Cancer Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…Accordingly, the increase of Nrf2 activity by several activators has been considered as a promising approach for preventing the development of vascular complications in diabetes. However, constitutive activation of Nrf2 has been also found in a variety of cancers; therefore, additional studies about the role of Nrf2 activation in specific tissues are necessary to better understand the multiple roles of Nrf2 in diabetes.…”
Section: Resultsmentioning
confidence: 99%